Penetration of magnetospheric electric fields to the equator and their effects on the low- latitude ionosphere during intense geomagnetic storms - Veenadhari, B.; Alex, S.; Kikuchi, T.; Shinbori, A.; Singh, Rajesh; Chandrasekhar, E. (My University, 2010)
The penetration of magnetospheric electric fields to the magnetic equator has been investigated for two intense magnetic storms that occurred on 31 March 2001 and 6 November 2001. The digital ground magnetic data from equatorial station Tirunelveli (TIR, 0.17Â°S geomagnetic latitude (GML)) and lowâ€ latitude station Alibag (ABG, 10.17Â°N GML) have been used to identify the storm time electrojet index, EEJ(Dis), which is the difference of the magnetic field variations between TIR and ABG after removing the quiet day variations. The appearance of enhanced DP 2 currents and counterelectrojets (CEJ) during the main and recovery phases of the magnetic storms is possibly due to prompt penetration of electric fields from the high latitudes. These signatures can be interpreted as a clear indicator of the eastward and westward electric fields at the equator. The observed results suggest that the magnitude of the equatorial ionospheric currents driven by the penetrating electric fields is very sensitive to ionospheric conductivity (which depends on local time). Moreover, the intensity of the DP 2 currents started decreasing during the end of the main phase of the storm despite the large negative southward IMF Bz, indicating the dominance of a wellâ€ developed shielding electric field for 1 h. As an effect of penetrating electric fields at the equator, the equatorial ionization anomaly is enhanced during the main phase (because of strong eastward electric field) and is inhibited or reduced due to the strong CEJ (because of westward electric field) during the recovery phase.
Keywords: Magnetospheric electric field; Low latitude ionosphere; Ionosphere; Geomagnetic storms; Electric fields; Trinelveli; Alibag; Equatorial ionospheric current; Geomagnetic latitude